Development of Experimental Protocol for Visual Cognitive Function Evaluation in Children with Autism Spectrum Disorders - Pereverzeva D.S; Gorbachevskaya N.L; Blagovechtchenski E.D (Moscow State University of Psychology and Education, 2016)
The article aims to present experimental protocol for investigation of visual cognitive function in children and adolescents with autism spectrum disorders. Description of experimental design is introduced by theoretical review of visual attention, perception and visual-motor control development in children with idiopathic autism and those with Fragile X mental retardation syndrome. Research method presented in the article is based on recent studies of visual cognitive function development under normal and pathological condition. The protocol includes three experimental paradigms: "antisaccade test", "big/ figures", and "photos test" performed by making use of eye tracking recording. This work was supported by grant RFBR 14-06-31284